Client psychology - Chaffin, Charles R. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2018)
A Client-Centered approach to Financial Planning Practice built by Research for Practitioners The second in the CFP Board Center for Financial Planning Series, Client Psychology explores the biases, behaviors, and perceptions that impact client decision-making and overall financial well-being. This book, written for practitioners, researchers, and educators, outlines the theory behind many of these areas while also explicitly stating how these related areas directly impact financial planning practice. Additionally, some chapters build an argument based solely upon theory while others will have exclusively practical applications. -Defines an entirely new area of focus within financial planning practice and research: Client Psychology -Serves as the essential reference for financial planners on client psychology -Builds upon and expands the body of knowledge for financial planning -Provides insight regarding the factors that impact client financial decision-making from a multidisciplinary approach If you're a CFP professional, researcher, financial advisor, or student pursuing a career in financial planning or financial services, this book deserves a prominent spot on your professional bookshelf.
About the contributors -- Introduction / Charles R. Chaffin, Ed. D, CFP Board Center for Financial Planning -- Client psychology -- Behavioral finance -- Behavioral finance -- Heuristics and biases -- Prospect theory -- The role of mental accounting in household spending and investing decisions -- Intentional choice architecture -- Cognition, distraction and the financial planning client -- Personality and financial behavior -- Risk literacy -- Automated decision aids : understanding disuse and designing for trust, with implications for -- Marriage and family therapy, financial therapy, & client psychology -- Client diversity : understanding and leveraging difference to enhance financial planning practice -- Client psychology : the older client -- Financial psychology -- Money disorders and other problematic financial behaviors -- Situation awareness in financial planning : research and application -- Final thoughts -- Index.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on March 14, 2018).
Keywords: Financial planning industry -- Customer services; Financial planning -- Psychological aspects; BUSINESS & ECONOMICS -- Finance; Electronic books